Education and Practice of Moderate Islam in The Pesantren Progressive Bumi Shalawat Sidoarjo - Bakhrul Huda (Postgraduate Program, State Islamic Institute (IAIN) Kediri, Indonesia, 2020)
Islam, according to the meaning of its name, is certainly synonymous with peace, but some Moslem direct it as a promoter of violence, chaos, and terror. Many teachings that are brought by the Prophet, perfected morality is an important point of his teachings that are escaped by his followers who like to spread violence, chaos, and terror. The concept of moderate Islam is not a new idea. It has been around since the Prophet taught it to his Companions. This can be explored from various historical literature and hadith texts. Especially in Indonesia, Moderate Islamic Education can always be found in Pesantren, not only ideas and concepts but also practices. This paper will try to explore how Moderate Islamic Education is taught and practised in Pesantren, especially in Pesantren Progressive Bumi Shalawat Sidoarjo. Pesantren which since its establishment in 2010 has been cooperating with ITCC (Indonesia Tionghoa Culture Center), AIESEC (Association Internationale des Etudiants en Sciences Economiques ET. Commerciales) and Japan Foundation to get a native speaker as a foreign language teacher and culture sharer. More than 15 people from various countries have been actively involved in becoming teachers in this Pesantren with various religious backgrounds. A tolerant and respectful attitude that is grown and developed from the school-age to become a moderate Muslim appears with the presence of the foreign teacher. With the case study method, the writer will analyze the existing situation in Pesantren Progresif Bumi Shalawat Sidoarjo related to moderate Islam which is taught and practised there.